Managing Obesity and Glucose Intolerance with Bariatric Surgery, An Experience in Birdem General Hospital - Faruq, Amreen; Husain, Muhd Mustaque; Zafar, SM Abu (BIRDEM Medical Journal, 2014)
Background: Weight reduction is the cornerstone for managing obesity and Type 2 diabetes. Bariatric surgery, a concept used worldwide and recently introduced in Bangladesh is effective in achieving significant weight loss, improving and resolving comorbidities. Materials and methods: This was a retrospective study thirty cases in whom bariatric surgery was carried out in the Department of Surgery in BIRDEM General Hospital were purposively sample for analysis. Results: Thirty patients were operated of whom 3 were male and 27 female with the mean age of 40 years. Preoperative mean BMI was 47.1 kg/m2, 83% patients had diabetes, 60% had hypertension. Twenty eight patients underwent laparoscopic sleeve gastrectomy, 1 gastric bypass and 1 open near-total gastrectomy with Roux-en-Y gastrojejunostomy. Postoperative mean BMI achieved was 34.4 kg/m2. in the first year. Fifty two percent of the diabetic patients are now in good glycemic control with minimum drugs and 48% are in complete resolution. Conclusion: Obesity and type 2 diabetes mellitus can be managed successfully with bariatric surgery. Birdem Med J 2014; 4(2): 70-73